2021
DOI: 10.3389/fdgth.2021.642818
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults Engage With Personalized Digital Coaching Programs at Rates That Exceed Those of Younger Adults

Abstract: Background: The US population is aging and has an expanding set of healthcare needs for the prevention and management of chronic conditions. Older adults contribute disproportionately to US healthcare costs, accounting for 34% of total healthcare expenditures in 2014 but only 15% of the population. Fully automated, digital health programs offer a scalable and cost-effective option to help manage chronic conditions. However, the literature on technology use suggests that older adults face barriers to the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 39 publications
2
29
0
Order By: Relevance
“…Studies have found that desire for human contact and technology literacy barriers can be deterrents for mental health app use, particularly among older adults; thus, more coaching may be beneficial for these users [ 55 , 109 ]. Moreover, others have found older adults to be more engaged with digital coaches than younger ones [ 110 ]. In contrast, rather than necessarily wanting more contact, adolescents may prefer different approaches; to illustrate, integrating peer support and strength-based messaging may be preferable [ 111 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that desire for human contact and technology literacy barriers can be deterrents for mental health app use, particularly among older adults; thus, more coaching may be beneficial for these users [ 55 , 109 ]. Moreover, others have found older adults to be more engaged with digital coaches than younger ones [ 110 ]. In contrast, rather than necessarily wanting more contact, adolescents may prefer different approaches; to illustrate, integrating peer support and strength-based messaging may be preferable [ 111 ].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has accelerated the creation and use of digital mental health resources across a variety of settings. As the veteran population in the United States is aging and their smartphone ownership is growing, they are also more successfully engaging with digital health products [ 23 ]. To our knowledge, this study is one of the first to document current smartphone ownership rates in the US veteran population, the majority of whom were older, and to examine predictors of uptake and usage of a mental health app focused on COVID-19–related stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Although older adults in the United States may be somewhat less likely than their younger counterparts to use mobile devices, the majority (61%) own smartphones [ 21 ]. Older adults express interest in using mobile devices to support health [ 22 ], and in some cases their engagement with digital health products may exceed that of younger adults [ 23 ]. In general, prior research suggests that older adults are interested in apps for health, but uptake and usage continue to be relatively low [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, older adults report willingness to engage with smartphone-based technologies for pain management ( 4 ). Moreover, recent research indicates that older adults show higher engagement with digital health programs than younger adults, contrary to conventional wisdom that older adults face too many barriers to engage with digital health programs at the same level as younger adults ( 5 ). The results from Graham and colleagues ( 5 ), comparing engagement in digital health programs of adults 35 to 64 years to those over 65, demonstrated that adults over 65 engaged in significantly more coaching conversations, logged more meals, and provided more connected device measurements than younger adults.…”
Section: Introductionmentioning
confidence: 81%